Geomechanical wellbore stability modeling of exploratory wells – study case at middle Magdalena basin: Modelamiento geomecánico de la estabilidad de pozos exploratorios-caso de estudio en la cuenca del Magdalena Medio - Carvajal Jiménez, Jenny Mabel; Valera Lara, Luz Carime; Rueda, Alexander; Saavedra Trujillo, Néstor Fernando (CT&F - Ciencia, Tecnología y Futuro, 2007)
This paper presents the geomechanical wellbore stability model of an exploratory well sited at Middle Magdalena Basin (MMB), which is based on the validity of linear elastic deformational theory for porous media; the use of correlations and field tools such as well and image logs to indirect determination of mechanical properties and stress state. Additionally, it is shown the model calibration and validation using drilling events which occurred at other previously drilled wells in the study area, at the exploratory well itself and experimentally evaluated mechanical properties on outcrop and core samples from the basin formations. This application allowed the Instituto Colombiano del Petróleo (ICP) at Ecopetrol S.A. to formally perform the geomechanical modeling of Colombian formations and to accomplish a complete and appropriate methodology to do so; such methodology has been standardized as part of the drilling support process at Ecopetrol S.A., supplying the possibility for taking decisions that contribute to reduce drilling costs and risks during operations.